Vibration control of a vehicle's seat suspension featuring a magnetorheological damper based on a new adaptive fuzzy sliding-mode controller. (March 2016) - Phu, Do Xuan; Choi, Seung-Bok; Lee, Yang-Sub; Han, Moon-Sihk
This work presents a new design for adaptive fuzzy sliding-mode control based on two methodologies, namely H ∞ control and sliding-mode control, and its control effectiveness. This is achieved by implementing a control scheme for vibration control of a vehicle with a seat suspension on which a magnetorheological damper is installed. The sliding surface of sliding-mode control is analysed by separation into two matrices: a Hurwitz-constants matrix and a constant matrix. These matrices are the basis for establishing the proposed control scheme combined with the H ∞ technique. The control scheme consisting of the combination of H ∞ control and sliding-mode control is reinforced by a new robustness function featuring an exponential function. In this work, a fuzzy logic model, which is well known to be an excellent model for uncertain dynamic systems, is integrated with the proposed control algorithm. The fuzzy logic model adopted in this work is an interval type-2 fuzzy model featuring fast computation of the output. The effectiveness of the proposed control scheme is evaluated through both computer simulations and experimental realization on a vehicle with a seat suspension which is equipped with a magnetorheological damper. In addition, in this work, two existing adaptive controllers are modified and implemented for comparative work with the proposed control scheme. It is shown that the proposed control scheme exhibits a much better vibration control performance than the two existing adaptive controllers do.